STUDENTS’ PERCEPTIONS TOWARD COLLABORATIVE LEARNING STRATEGY FOR OVERCOMING SPEAKING ANXIETY AMONG STUDENTS OF AN ISLAMIC SENIOR SCHOOL - Farizatul Aini; Muhammad Amin; Agus Saputra (Journal of English Education Forum (JEEF), 2022)
Anxiety is one of the most frequent problems in speaking a foreign language including English. High levels of anxiety prevent students from speaking English fluently. Therefore, teachers need to apply a strategy that can reduce these anxieties. One of the strategies is the collaborative learning strategy. This research aimed to find out students’ perceptions toward collaborative learning strategies for overcoming speaking anxiety. The research was conducted on eleventh-grade students at an Islamic Senior School in East Lombok regency. The total number of samples in this research was 33 students from XI social 4 class. This study was qualitative in nature since it used observation, a questionnaire, and an interview to collect the data. Students’ perception of using collaborative learning in learning speaking reached 85.5% based on the students' responses to the questionnaire, while data from the observation and interview reveal that the perception of using collaborative learning strategy in overcoming students’ speaking anxiety was positive because it can increase students’ confidence, help the students to understand the material easier, and make the students more active in the class. It can be concluded that collaborative learning strategy can help students to overcome their speaking anxiety.